Hubungan pengetahuan ibu tentang diare dengan kejadian dehidrasi Pada pasien anak dengan diare - Desi Kurniawati; Devi Christiawati; Yusnita Yusnita (THE JOURNAL OF Mother and Child Health Concerns, 2024)
Background: In Indonesia, diarrhea with complications of dehydration is still a cause of death in toddlers. In South Lampung Regency, diarrhea cases are included in the 10 largest diagnoses in seventh place. One of the factor's causing diarrhea is parental knowledge. Purpose: To determine the relationship between maternal knowledge about diarrhea and the incidence of dehydration in children with diarrhea. Method: Correlation design with crossetional approach. The population of this study were all mothers who had toddlers who experienced diarrhea at Natar Medika Hospital. Based on the monthly report of Natar Medika Hospital from July 2023 to September 2023, the population size of pediatric patients with diarrhea was 44 cases with a non-probability sampling technique, namely purposive sampling of 39 people. Results: get maternal knowledge about diarrhea good results 27 people (70%) children have diarrhea without dehydration 34 people (90%). Based on bivariate analysis obtained p-value 0.029. Conclusion: There is a relationship between maternal knowledge about diarrhea and the incidence of dehydration in Natar Medika Hospital in 2023, namely in mothers with good knowledge their children do not experience dehydration. Keywords: Dehydration; Diarrhea; Mother Knowledge. Pendahuluan: Di Indonesia diare dengan komplikasi dehidrasi masih menjadi penyebab kematian pada balita, Di Kabupaten Lampung Selatan kasus diare masuk dalam 10 diagnosa terbesar di urutan ke tujuh. Faktor penyebab diare salah satunya adalah pengetahuan orang tua. Tujuan: Untuk mengetahui hubungan pengetahuan ibu tentang diare dengan kejadian dehidrasi pada pasien anak diare. Metode: Desain korelasi dengan pendekatan crossetional. Populasi penelitian ini seluruh ibu yang mempunyai balita yang mengalami diare di RS Natar medika. Berdasarkan laporan bulanan RS Natar Medika dari Juli 2023 sampai dengan September 2023, didapatkan besaran populasi pasien anak dengan diare sebanyak 44 kasus dengan dengan tehnik sampling non probability sampling yaitu purposive sampling sebanyak 39 orang. Hasil: dapatkan pengetahuan ibu tentang diare hasil baik 27 orang (70%) anak mengalami diare tanpa dehidrasi 34 orang (90%). Berdasarkan analisa bivariat didapat p-value 0.029. Simpulan: Ada hubungan antara pengetahuan ibu tentang diare dengan kejadian dehidrasi di RS Natar Medika tahun 2023, yaitu pada ibu dengan pengetahuan yang baik anaknya tidak mengalami dehidrasi. Kata Kunci: Dehidrasi; Diare; Pengetahuan Ibu.